The optimal opening ratio of the internal diaphragm of the beam to CFRST column connection. (October 2022) - Xia, Chengxin; Cheng, Tianxi; Li, Shuo; Liu, Mei; Liu, Fangzhou; Wang, Peijun
Abstract: To reduce the obstructive effect of the internal strengthening diaphragm to the pumping concrete during the construction of the concrete-filled rectangular steel tubular column, an optimization suggestion and method for the opening ratio of the internal strengthening diaphragm are proposed. The finite element analysis method was used to study the factors that affect the opening ratio of the internal strengthening diaphragm. It was found that the main factors affecting the opening ratio of the internal strengthening diaphragm are the ratio of the beam width to the column width, the beam layout, and the thickness of the internal strengthening diaphragm. Based on the above parameter analysis, a method to determine the optimal opening ratio of the internal strengthening diaphragm is proposed. In addition, two new forms of internal strengthening diaphragm are proposed, which are the octagonal internal strengthening diaphragm and cross-shaped internal strengthening diaphragm. Under the condition of satisfying the design principle of equal strength and deformation limitation, the octagonal internal strengthening diaphragm can obtain a larger opening ratio and smaller column deformation than the traditional internal strengthening diaphragm. Under the condition of satisfying the deformation restriction, the cross-shaped internal strengthening diaphragm can further increase the opening ratio of the internal strengthening diaphragm.